Analysis of the dissipative behavior of steel beams for braces in three-point bending. (1st October 2021) - Gusella, Federico; Orlando, Maurizio
Highlights: Three-point bending tests to investigate the behaviour of steel beams are performed. The influence of design parameters on the member energy dissipation is investigated. The effect of the cross-section compactness and member slenderness is explored. Different cross-sections belonging to class 1 show different rotation and failure mode. The seismic performance and adequacy of tested beams as braces is highlighted. Abstract: In the capacity design method, earthquake resistant structures should have the ability to dissipate energy in plastic mechanisms through dissipative zones, which are expected to yield while the others remain in the elastic range during seismic excitation. In this paper, the elastoplastic response of different steel beams in three-point bending, under monotonic and cyclic loads, is investigated through experimental tests and theoretical analysis to investigate their efficacy to be used as fuses in an innovative bracing system. Results provide useful information on the influence of several design parameters such as the geometrical properties of members, the steel strength-strain behavior, the connection structural details and the geometric non-linearity. The stability of the moment-rotation hysteretic loops and the energy dissipation is assessed through cyclic tests. The influences of the cross-section compactness and member slenderness are also investigated. Within the "Design Assisted by Testing" framework, the results highlight the role of member cross-section shape. Double channel sections have a greater rotation capacity than rectangular hollow sections with the same elastic section modulus and of the same section class. Moreover, the influence of the connection details is explored. To promote the utilization of the proposed bracing system, the work concludes with design recommendations.